STRATEGI GURU PAI DALAM MENGELOLA KELAS UNTUK MENGHASILKAN PEMBELAJARAN YANG EFEKTIF PADA SISWA KELAS VIII DI SMPN 05 SEMPARUK TAHUN AJARAN 2023-2024 - Nadiya Nadiya; Susilawati, Mauizatul Hasanah (ADISAM PUBLISHER, 2024)
The aim of this research is to reveal: 1) PAI teachers' strategies in managing classes for class VIII students at SMPN 05 Semparuk for the 2023-2024 academic year; 2) PAI teacher strategies produce effective learning for class VIII students at SMPN 05 Semparuk for the 2023-2024 academic year; and 3) Supporting and inhibiting factors for PAI teachers in managing classes for class VIII students at SMPN 05 Semparuk in the 2023-2024 academic year. This research uses a descriptive approach and qualitative research type. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data display, data verification and drawing conclusions. The data checking and validity techniques used are triangulation and member checking. Based on the data analysis carried out, the research results show that; (1) The PAI teacher's strategy in managing classes for class VIII students at SMPN 05 Semparuk for the 2023-2024 academic year consists of several steps, namely planning, organizing, acting, and evaluating.( 2) PAI teacher strategies produce effective learning for class VIII students at SMPN 05 Semparuk for the 2023-2024 academic year. consists of several steps, namely: using experiential learning strategies where inviting students to learn while playing with the aim of making children not get bored during learning, and using direct learning strategies, apart from delivering material using the lecture method, teachers also often use media in the learning process. (3) There are two supporting and inhibiting factors for PAI teachers in managing classes for class VIII students at SMPN 05 Semparuk for the 2023-2024 academic year, namely: First, factors that support PAI teachers in managing classes are facilities such as wifi, infocus, classrooms, and books, and the second factor that supports managing the classroom from school factors is strong support from school management, including the principal and fellow teachers. Factors that hinder PAI teachers in managing the class are that there are several students who chat and often come in and out of the class, and limited teaching time.